New Orchids (Orchidaceae: Epidendroideae and Vandoideae) in the Flora of Vietnam - Leonid V. Averyanov (Taiwania, 2018)
The paper continues our recent publication of new original data on orchid diversity in Vietnam (Averyanov et al., 2018a-c) obtained in 2016–2017. It includes data on 5 orchid species new for science (Calanthe nguyenthinhii Aver., Dendrobium truongcuongii Aver. et Canh, Gastrodia khangii Aver., Nephelaphyllum thaovyae Aver. et Canh and Podochilus truongtamii Aver. et Vuong) and 15 species, new for the flora of Vietnam (Calanthe ceciliae, Dendrobium eriiflorum, D. griffithianum, D. hekouense, D. minusculum, D. stuposum, D. xichouense, Eria lancifolia, E. xanthocheila, Geodorum terrestre, Liparis condylobulbon, L. tenuis, Luisia teres, Pomatocalpa maculosum, Porpax ustulata). Annotated species list includes the valid name, synonyms, type, citations of relevant taxonomic regional publications, data on ecology, phenology and distribution, estimated IUCN Red List status, studied specimens, brief taxonomic notes, and illustrations for each recorded species. Lectotypes for two species, Liparis tenuis, and Dendrobium exsculptum are proposed. When the new data presented in this paper are included, the documented orchid flora of Vietnam reaches at least 1243 species.